WEBSITE TRANSFER PAPER MAKING USING MICROSOFT FRONTPAGE 2003 - Hadi Abdullah; Ire Puspa.W, Ir, MMSI Ire Puspa.W, Ir, MMSI (Jurnal Sistem Informasi, 2005)
Website Creation Transfer Paper By Using Microsoft FrontPage 2003 is a WorldWide Web application that contains information about how to create an image on a Tshirtwith Transfer Paper, which is packaged into an attractive and interactive formcreated using Microsoft FrontPage 2003. It is expected that these applications canhelp users of this web page to find additional information about how to use TransferPaper.Using Microsoft FrontPage 2003, this application is the combination of elements ofweb pages are pictures, and hyperlink text, which are summarized into a singleapplication into a form that is expected to easily be used by anyone and is made asattractive as possible while using this application. By simply clicking on one of theoptions from the menu the user will immediately get the information quickly.